Protective effect of Aqueous Extract of Ginger against Mitronidazole Induced Chromosomal aberration in bone marrow cells and sperm abnormalities in Albino Rats - Ismail, Narmeen Abdulsamad (Diyala Journal of Medicine, 2019)
Background: A wide variety of phenolic substances derived from spice possess potent antimutagenic and anticarcinogenic activities. Some of these phenolic substances are present in ginger, possessing strong anti-inflammatory and anti-oxidative properties as well as exert substantial anti-carcinogenic and anti-mutagenic activities. Objective: The aim of the present study to exam the protective effect of ginger extract on Metronidazole (MT) induce bone marrow chromosomal aberrations and sperm abnormalities, cell inoculated in male albino rats. Patients and Methods: The present experiment included four groups of male albino rats. The experimental group was administered five consecutive oral dose of metronidazole (250mg/kg/day). The subsequent experimental group was administered ginger extract (150mg/kg/day) for 9 days and on the 10th day Metronidazole (250mg/kg/day) was administered for five consecutive days. For each experimental group a parallel control group was maintained, one group administered 1ml of D.W. for 14 days the seconded group administered (150mg/kg/day) of ginger extract for 9 days . Twenty two hours after the administration of the last dose, rats were sacrificed for both chromosomal aberration and sperm abnormalities. Results: In animals treated with only mitronidazole there was a significant increases of chromosomal aberration and sperm abnormalities. mitronidazole, beside other chromosomal aberrations such as polyploidy, anuploidy were also observed. In comparison to normal group animals were pre-treated with plant extract and subsequently treated with mitronidazole and an overall decline in the mutation rate was also discernible clearly indicating the protective effect of plant extract. Conclusion: the results of this study indicate that metronidazole has the ability to induce chromosome aberrations including (centromeric breake, centromeric gap, chromatid break, centromeric fusion, polyploidy, aneuploidy and chromatid gap) in bone marrow cells and sperm abnormalities in male albino rats. Ability of aqueous extract of ginger to reduce both chromosomal aberrations and sperm abnormalities of mutated rats